Relevance of Detail in Basal Topography for Basal Slipperiness Inversions: A Case Study on Pine Island Glacier, Antarctica - Kyrke-Smith, Teresa M.; Gudmundsson, G. Hilmar; Farrell, Patrick E. (Frontiers in Earth Science, 2018)
Given high-resolution satellite-derived surface elevation and velocity data, ice-sheet models generally estimate mechanical basal boundary conditions using surface-to-bed inversion methods. In this work, we address the sensitivity of results from inversion methods to the accuracy of the bed elevation data on Pine Island Glacier. We show that misfit between observations and model output is reduced when high-resolution bed topography is used in the inverse model. By looking at results with a range of detail included in the bed elevation, we consider the separation of basal drag due to the bed topography (form drag) and that due to inherent bed properties (skin drag). The mean value of basal shear stress is reduced when more detailed topography is included in the model. This suggests that without a fully resolved bed a significant amount of the basal shear stress recovered from inversion methods may be due to the unresolved bed topography. However, the spatial structure of the retrieved fields is robust as the bed accuracy is varied; the fields are instead sensitive to the degree of regularisation applied to the inversion. While the implications for the future temporal evolution of PIG are not quantified here directly, our work raises the possibility that skin drag may be overestimated in the current generation of numerical ice-sheet models of this area. These shortcomings could be overcome by inverting simultaneously for both bed topography and basal slipperiness.